Estimation of combining ability and heterosis in TGMS based two-line hybrids of rice (Oryza sativa) - K, SAI REKHA; R, SARASWATHI; M, KUMAR; M, RAVEENDRAN; S, ROBIN (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during summer and rainy (kharif) season of 2016 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to study general combining ability (gca) and specific combining ability (sca) and the level of heterosis using Indica/tropical japonica male parents by crossing with TGMS lines. During the study five thermosensitive genic male sterile (TGMS) lines and eight male fertile lines (4 Japonica and 4 Indica) were used to produce 40 hybrids. The combining ability and standard heterosis were analysed for 10 characters, viz. days to 50% flowering, plant height, number of productive tillers/plant, panicle length, number of filled grains/panicle, 100-grain weight, spikelet fertility%, single plant yield, harvest index and biomass yield. The results revealed that the lines, TNAU 95S and TNAU 14S, tropical japonica tester Palawan and indica tester CB 15137 showed positive significant gca effect for about five characters. These cultures can be utilized as parents in hybridization programmes due to their high general combining ability for over five characters. The eight hybrids namely, TNAU 14S × Palawan; TNAU 14S × KhaoKap Sang; TNAU 14S × CB 13212; TNAU 14S × CB 15137; TNAU 18S × CB 15117; TNAU 45S × Khao do ngoi; TNAU 45S × KhaoKap Sang; and TNAU 60S × Khao do ngoi showed significant sca effects for more than 4 characters and were found to be promising hybrids based on specific combining ability. Four hybrids selected with high standard heterosis for more than 5 characters, viz. TNAU 14S × AC 38479, TNAU 14S × CB 15121, TNAU 45S × CB 15137 and TNAU 95S × CB 15121 were considered as best hybrids and can be further used in heterosis breeding.